PENGARUH PROFITABILITAS DAN LIKUDITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA SUB SEKTOR FARMASI TERDAFTAR DI BEI - Rita Sarlawa; Solikah Nurwati; Resa Purna Susanti (LPSDI Bina Patria, 2022)
This study aims to determine the analysis of the influence of Profitability and Liquidity on Dividend Policy with Capital Structure as an Intervening Variable in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange. The sample in this study were 6 companies using the purposive sampling method. The analysis technique uses Partial Least Square (PLS). The results show that Profitability has a significant positive effect on dividend policy. Liquidity has no significant negative effect on dividend policy. Profitability has no significant positive effect on capital structure. Liquidity has a significant negative effect on capital structure. Capital structure has no significant positive effect on dividend policy. Profitability has no significant effect on dividend policy through capital structure as an intervening variable. Liquidity has no significant effect on dividend policy through capital structure as an intervening variable. For further research, it is recommended to use more independent variables, it is also recommended to conduct research on companies with more diverse characteristics, so that the results obtained can be representative for conclusions to be drawn by comparing each sector of the companies listed on the Indonesia Stock Exchange.